Modelling phytoplankton and bacterial loop dynamics during sea-ice retreat in the Scotia- Weddell Sea area: Tentative budget of carbon cycling at the first trophic levels of the planktonic ecosystem - Lancelot, Christiane; Billen, Gilles; Veth, Cornelis; Becquevort, Sylvie; Mathot, Sylvie (1992)
info:eu-repo/semantics/published